Health Assessment of Chicken Meat Contamination by Salmonella in Markets of Raqqa City (Journal of Hama University, 2025)
This study aimed to determine the prevalence of contamination by Salmonella in Chicken meat in the markets of Raqqa city. The study was conducted on 200 samples of Chicken meat offered for sale in shops in the markets of Raqqa city, which were collected randomly from different parts of Chicken meat (breast – thigh – wing – liver) with equal numbers.The results of bacterial isolation and biochemical tests showed that 42 samples of Chicken meat out of 200 samples taken from the markets of Raqqa city were positive. The overall prevalence of contamination by Salmonella in chicken meat in Raqqa city was 21%. The highest prevalence of contamination by Salmonella was in the liver, reaching 34%, while the lowest prevalence of contamination by Salmonella  was in the wing, where it amounted to 14%. These results are an indication of a risk on the health of consumers, as Salmonella is among the pathogens of foodborne diseases, which threat public health in community.